Prevalence of Hepatitis B&C in Pregnant females &Transmission through Sporadic Source and Dental Source among Pakistani Population: A Brief Review - Aasia Zahid, Hina Awais, Fareeha Bashir, Talha Mannan, Ayesha Afzaal, Nauman Khokhar, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Hepatitis refers to liver inflammation because it can be cause by drugs,chemicals, heavy alcohol consumptionand due to some medical disorders. The hepatitis B (HBV) is a double stranded DNA virus having multiple serological indicators whereas hepatocellular carcinoma is assumed to be significantly influenced by hepatitis C viral infection. Aim: To evaluate the frequency of hepatitis B & C in pregnant females as well as how many people were affected through dental clinics and sporadic sources in Pakistan. Methods:All the data for this review article was collected from different databases such as Google scholar, PubMed, Pak Medinet and Medline. Findings:In Pakistan, the occurrence of hepatitis B infection is alarmingly rising, ranging from 2 to 8% in various populations. 20.2% in urban, while 79.8% in rural regionwhereas HCV affects almost 8.74 million people in Pakistan. Practical Implication& Conclusion: The foremost purpose of this systematic review was to assessment the frequencyof hepatitis B and C among Pakistani population from already reported data and concluded that the rate of spread of hepatitis B,C through sporadic sources and dental source is also a well-known factor in Pakistani population. So as this review would be helpful for those researchers who work on the hepatitis control program in the Pakistan. Keywords:Barber source,Dental source, Hepatitis B, Hepatitis C, Prevelance, Transmission